PROGRAM PELATIHAN PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO PEMBELAJARAN - Agus Hadi Utama; Agus Salim (Journal of Innovation Research and Knowledge, 2021)
In the era of the industrial revolution 4.0 and the Covid-19 pandemic, the creativity of digitally created learning content is a must to increase the effectiveness of online learning. Students can learn effectively when they are enthusiastic in the learning process. The enthusiasm of students is influenced by the motivation obtained through learning media such as videos. The continuity of the online learning process that is being implemented in the era of the COVID-19 pandemic cannot be separated from the role of educational institutions that provide education itself. Digital learning content is an important part of the process, teachers should be able to provide good digital learning content for students. The tendency of teachers who is more dominant to use existing learning video media rather than editing learning videos creatively results in the incomplete learning message being delivered to students. This research methodology is a type of qualitative research model evaluation of the CIPP program (Context, Input, Process, Product) in the training program for developing video-based teaching materials for teachers in schools who are members of the K3SD communication forum in Central Banjarmasin district to be able to look for alternative solutions in planning and implementing appropriate online learning during the covid-19 pandemic. This research activity resulted in 1) Dissemination of alternative online learning solutions that were more practical and efficient through the development of PowerPoint teaching materials into learning videos. 2) A training program to equip teachers who are members of the K3SD communication forum in developing PowerPoint teaching materials into learning video media. 3) Produce effective video-based teaching outputs for online learning during the covid-19 pandemic.